Ubiquitin-like modification dependent proteasomal degradation and disease therapy - Wang, Tiantian; Jiang, Jie; Zhang, Xue; Ke, Xisong; Qu, Yi (Trends in molecular medicine, 2024)
Many proteins have been identified subject to ubiquitin (Ub)-independent proteasome degradation (UbIPD), a process mediated by Ub-like (UBL) proteins.UBL-conjugates can be processed by 19S proteasomes by mechanisms different from Ub-conjugates and by proteasome activator 28γ, which was previously thought to work as an activator of UbIPD.Ub and UBLs coordinate proteasome degradation to maintain protein homeostasis.UBL proteins, enzymes and modification substrates are tightly associated with proteostasis in muscle and neurodegenerative diseases. Although it is believed that ubiquitin (Ub) modification is required for protein degradation in the proteasome system (UPS), several proteins are subject to Ub-independent proteasome degradation, and in many cases ubiquitin-like (UBL) modifications, including neddylation, FAT10ylation, SUMOylation, ISGylation, and urmylation, are essential instead. In this Review, we focus on UBL-dependent proteasome degradation (UBLPD), on proteasome regulators especially shuttle factors and receptors, as well as potential competition and coordination with UPS. We propose that there is a distinct UBL–proteasome system (UBLPS) that might be underestimated in protein degradation. Finally, we investigate the association of UBLPD with muscle wasting and neurodegenerative diseases in which the proteasome is abnormally activated and impaired, respectively, and suggest strategies to modulate UBLPD for disease therapy. Although it is believed that ubiquitin (Ub) modification is required for protein degradation in the proteasome system (UPS), several proteins are subject to Ub-independent proteasome degradation, and in many cases ubiquitin-like (UBL) modifications, including neddylation, FAT10ylation, SUMOylation, ISGylation, and urmylation, are essential instead. In this Review, we focus on UBL-dependent proteasome degradation (UBLPD), on proteasome regulators especially shuttle factors and receptors, as well as potential competition and coordination with UPS. We propose that there is a distinct UBL–proteasome system (UBLPS) that might be underestimated in protein degradation. Finally, we investigate the association of UBLPD with muscle wasting and neurodegenerative diseases in which the proteasome is abnormally activated and impaired, respectively, and suggest strategies to modulate UBLPD for disease therapy.